PELESTARIAN MAKAM SYEKH ABDURRAHMAN SIDDIQ MELALUI PENGENALAN HUKUM TATANEGARA - Ali Azhar; KMS Novyar Satriawan Fikri; Marlina (JURNAL PENGABDIAN MANDIRI, 2023)
Because of its history and culture, which shed light on a prominent religious figure from Riau's earlier days, the village of Teluk Dalam possesses a unique potential for cultural significance. Despite this, the area has not been able to properly manage the tourism potential or make money from it. In order to uncover new tourist attractions, conserve and document historic structures and artifacts, and package tourist attractions for performances at village festivals, the team devised cultural preservation efforts through community support programs. Debriefing, coaching, and training are all forms of assistance that are utilized in this process. After then, the attractions are promoted through various social media platforms. Because of the results of the mentorship programs, there has been a rise in cultural preservation knowledge, expertise, and concern. All of these factors have an effect on the possible new sources of income for the community. The village festival celebrations in Teluk Dalam Village do an excellent job of preserving numerous cultural traditions in addition to historical legacies.